Tetraspanin Scaffold Proteins Function as Key Regulators of Hematopoietic Stem Cells - Balise, Victoria D.; Saito-Reis, Chelsea A.; Gillette, Jennifer M. (Frontiers in Cell and Developmental Biology, 2020)
Hematopoietic stem and progenitor cells (HSPCs) are responsible for the development, maintenance, and regeneration of all the blood forming tissues in the body, and as such, are critical for a number of patient therapies. For successful HSPC transplantation, stem cells must traffic through the blood and home to the bone marrow microenvironment or “niche”, which is composed of soluble factors, matrix proteins, and supportive cells. HSPC adhesion to, and signaling with, cellular and extracellular components of the niche provide instructional cues to balance stem cell self-renewal and differentiation. In this review we will explore the regulation of these stem cell properties with a focus on the tetraspanin family of membrane proteins. Tetraspanins are molecular scaffolds that uniquely function to distribute proteins into highly organized microdomains comprising adhesion, signaling, and adaptor proteins. As such, tetraspanins contribute to many aspects of cell physiology as mediators of cell adhesion, trafficking, and signaling. We will summarize the many reports that identify tetraspanins as markers of specific HSPC populations. Moreover, we will discuss the various studies establishing the functional importance of tetraspanins in the regulation of essential HSPC processes including quiescence, migration and niche adhesion. When taken together, studies outlined in this review suggest that several tetraspanins may serve as potential targets to modulate HSPC interactions with the bone marrow niche, ultimately impacting future HSPC therapies.